Estimation of upper flammability limits of C-H compounds in air at standard atmospheric pressure and evaluation of temperature dependence - Mendiburu, Andrés Z. [UNESP]; de Carvalho, João A. [UNESP]; Coronado, Christian R. (Elsevier, 2016)
This study focuses on estimating the upper flammability limits of C-H compounds. A method was developed to determine the upper flammability limits in air at standard atmospheric pressure for the following cases: (a) estimation of the UFLs of pure C-H compounds at standard ambient temperature (25. °C); (b) estimation of the UFLs of binary mixtures of C-H compounds at standard ambient temperature (25 °C); (c) estimation of the UFLs of C-H compounds at different initial temperatures. The method was accurate in all cases. In case (a), for a total set of 115 compounds, the absolute average relative error was 7.27% and a squared correlation coefficient of 0.9248 was obtained. In case (b), the average absolute relative error was 5.55%; in case (c) it was 2.19%.
Keywords: C-H compounds; Estimation; Initial temperature effect; Upper flammability limits